Metabolism effector links in diet-induced and genetically-based obesity: A full-transcriptome study of liver tissue in experimental models in rodents - S. A. Apryatin; N. V. Trusov; I. V. Gmoshinski; V. A. Tutelyan (Acta Biomedica Scientifica)
Background. When developing methods for personalized diet therapy of obesity, an urgent task is to study the molecular genetics features of the obesity pathogenesis using in vivo experimental models in laboratory animals.The aim. To determine metabolism effector links in obesity based on a comparative analysis of full-transcriptome profiles of the liver tissue of mice and rats of various strains.Materials and methods. We carried out a comparative analysis of the changes in liver transcriptome in rats and mice fed with diets of excessive energy value and exerting lipogenic effect. Data of full-transcriptome profiling using DNA microarray technology have been presented previously in 8 publications.Results. In three strains of mice treated with a high-carbohydrate high-fat diet (HCHFD), a significant differential expression (DE) of 1849 genes was revealed, of which 74 genes responded jointly in at least two groups of animals. In Wistar and Zuckerfa rats, 2109 genes responded to the consumption of HCHFD, of which 242 genes responded jointly in two groups of animals. For rodents different in genetic predisposition to the development of diet-induced obesity, the groups of genes that responded with the opposite sign of DE (depending on the genotype) in reaction to the consumption of HCHFD were identified. Bioinformatical analysis allowed establishing the presence of 43 metabolic pathways, which are targeted for the applied experimental diets exposure, in rats and 77 pathways – in mice. Four of these pathways – the pathway of retinoid metabolism, PPAR signaling pathway associated with it the previous one, xenobiotics metabolism and drugs metabolism mediated by cytochrome P450 system – responded in all groups of animals (except for female mice). The importance of the expression of Tat gene encoding tyrosine aminotransferase in the modulation of biogenic amines synthesis in diet-induced obesity was shown, which may represent a new neurometabolic regulatory function of the liver in response to the consumption of high-calorie diets.Conclusion. The analysis of the results of full-transcriptome studies showed that within each studied species (Rattus rattus and Mus domesticus) and animal sex, a number of genetic variants with a greater or lesser predisposition to the development of diet-induced obesity phenotype can be identified; and at the same time, within these variants, there is a largely similar pattern in the response of metabolism effector links to hypercaloric dietary intake. This pattern creates new prospects for translating the results of transcriptomic and metabolomic studies of laboratory animals into clinical practice in order to substantiate new approaches to personalized diet therapy of alimentary dependent diseases in patients with different genetic predisposition to obesity.